Janus-MoS < 2 >-coated CS / PI composite aerogel as well as preparation method and application of Janus-MoS < 2 >-coated CS / PI composite aerogel

PI aerogel was prepared by electrospinning and sol-gel-freeze-drying technology, and combined with electrostatic spraying technology, MoS2@CS dispersion was added to prepare Janus-MoS2@CS/PI composite aerogel, which solved the traditional ion exchange The problems of low membrane reverse osmosis efficiency and high energy consumption achieve efficient seawater desalination and real-time ion concentration detection.

CN119431876APending Publication Date: 2025-02-14KAILI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446931.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional ion exchange membranes have low reverse osmosis efficiency and high energy consumption in seawater desalination.

Method used

Polyamic acid (PAA) nanofiber membranes were prepared by electrospinning technology, and polyimide (PI) aerogel was prepared by sol-gel-freeze-drying technology, and then the MoS2@CS dispersion was coated by electrostatic spraying technology. Janus-MoS2@CS/PI composite aerogel was prepared by cloth on PI aerogel.

Benefits of technology

The composite aerogel exhibits efficient evaporation rate and evaporation efficiency in seawater desalination, and has good salt resistance, which can detect ion concentrations in water in real time, overcoming the disadvantages of traditional membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431876A_ABST
    Figure CN119431876A_ABST
Patent Text Reader

Abstract

The invention discloses a Janus-MoS2-coated CS / PI composite aerogel as well as a preparation method and application thereof, and belongs to the technical field of composite material preparation. Aiming at the problems of low reverse osmosis efficiency and high energy consumption of a traditional ion exchange membrane, the preparation method comprises the following steps: preparing polyimide aerogel from a polyamide acid nanofiber membrane prepared by an electrostatic spinning technology through a sol-gel-freeze drying technology; the preparation method comprises the following steps: preparing a MoS2 nanoflower precursor solution through a hydrothermal method, carrying out gradient heat treatment on the MoS2 nanoflower precursor solution, then adding chitosan alcohol, and carrying out ultrasonic treatment to obtain a MoS2 (at) CS dispersion liquid; electrostatic spraying is conducted on the polyimide aerogel through electrostatic spraying, and the Janus MoS2 coated CS / PI aerogel with the self-powered function, the signal transmission effect and the seawater desalination effect is obtained after drying. The aerogel shows good evaporation efficiency, excellent evaporation rate and relatively good salt resistance, and meanwhile, the defect that the ion concentration in water cannot be detected in real time by a traditional seawater desalination film is overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite material preparation, and specifically relates to a Janus-MoS2@CS / PI composite aerogel and a preparation method and application thereof. Background Art

[0002] In recent years, the Internet of Things, sensor electronics and smart wearable devices have been greatly developed and widely used. It is becoming increasingly important to power these devices through sustainable energy harvesting methods. Human limb movements such as arm movement, wrist bending, walking and jumping contain a lot of mechanical energy. Piezoelectric materials can collect the mechanical energy generated by human movement to provide green and continuous power for electronic devices. In recent years, piezoelectric electronic devices with the ability to absorb mechanical energy have received widespread attention and have shown broad application prospects in the fields of wearable electronic devices, health monitoring equipment and smart sensors. Due to its simple structure, high efficiency, self-powered, good controllability and other advantages, piezoelectric nanogenerators (PENGs) are widely used in energy harvesting, environment, health monitoring and other fields.

[0003] Polyimide (PI) is a polymer containing an imide ring on the main chain, the most important of which is a polymer containing a phthalimide structure. Due to its excellent properties such as strong mechanical properties, stable heat resistance, high transparency, high insulation, and low dielectric loss, PI shows broad application prospects. At the same time, PI also exhibits properties such as heat resistance, cold resistance, chemical environment resistance, and fatigue resistance, which greatly broadens its application range in extreme environments. People have studied and explored PI-based PENG for energy harvesting and fire detection in high temperature environments. For example, Li et al. introduced disulfide bonds and PDMS into the PI main chain and designed and synthesized a new type of self-healing PI. This self-healing PI-based TENG device has an open circuit voltage of 124V, a short circuit current of 0.75µA, and a short circuit charge of 47nC. Yan et al. used chemical vapor deposition to in situ grow carbon nanotubes (CNTs) on barium titanate (BTO) nanoparticles to prepare CNT@BTO nanomaterials, and incorporated them into PI nanofiber membranes. When the BTO content was 26wt% and the CNT content was 2wt%, the open circuit voltage and short circuit current of TENG based on PI / CNT@BTO nanofiber membranes were 305V and 104μA, respectively. In addition, TENG was integrated into a real-time temperature sensing alarm system. When the thermistor was heated, the circuit was turned on and the alarm buzzer was activated, thereby achieving the effect of fire warning.

[0004] In addition, the growing global population and the large-scale expansion of urbanization, industrialization, and agricultural upgrading are exacerbating the challenge of freshwater scarcity. Freshwater resources available for direct human use account for less than 0.36% of the total water resources. More than 1.7 billion people living in economically backward areas do not have access to standard drinking water, and 300 million people face food insecurity due to water shortages. Seawater, as the most abundant water source on Earth, accounts for 97.5% of the Earth's water resources. Therefore, seawater desalination is the most direct and effective strategy to solve existing problems. In the past decade, solar interfacial evaporation desalination, as one of the solar water production technologies, has received widespread attention in recent years due to its environmental protection, renewable, economical and efficient characteristics. The improvement of solar interfacial evaporation technology capabilities is mainly focused on the research of photothermal conversion materials and structural engineering. For example, Yuan et al. developed a nanofiber sponge solar interfacial evaporator that can produce water at room temperature under sunlight (1kW m -2 ) irradiated, the water evaporation rate of the interfacial evaporation system was 1.57 kg m -2 h -1 , the evaporation efficiency is 95.6%; for salt ions (Na + Mg 2+ , Ca 2+ and K + ) removal rate is 98.2%~99.5% and heavy metal ions (Cu 2+ 、Zn 2+ and Cd 2 + ) removal rate is 81.6%~98.2%, showing excellent water purification ability.

[0005] In recent years, in order to break through the limitation of theoretical efficiency, solar-driven interfacial evaporators have been extended from simple two-dimensional planar structures to three-dimensional hierarchical structures. Compared with two-dimensional planar evaporators, three-dimensional evaporators greatly reduce heat loss and can obtain a steady stream of energy from the environment, thereby significantly improving the evaporation rate and efficiency. Recently, aerogel is a material with a three-dimensional porous network structure, which has the advantages of extremely low density, high porosity and low thermal conductivity. Importantly, the raw materials for preparing aerogels are abundant, environmentally friendly and cheap. Its network framework contains abundant hydrophilic groups (-OH, -NH2, -COOH, etc.), and its hydrophilic functional groups can combine with water molecules to achieve excellent water transport performance. Therefore, aerogel has become a potential interfacial evaporator material for seawater desalination. Among many aerogels, the upper and lower surfaces of Janus aerogel have diametrically opposite hydrophilicity and hydrophobicity. The hydrophilic surface can provide continuous water upward through capillary force; while the hydrophobic surface plays the role of capturing sunlight, converting the absorbed solar energy into thermal energy, causing water to evaporate locally, and providing a channel for the escape of steam. For example, Zhang et al. designed a vertically arranged Janus MXene aerogel with a hydrophobic upper layer and a hydrophilic lower layer; compared with irregular porous channels, this adjustable and ordered vertically arranged structure has competitive advantages in capillary water transport, light absorption and water vapor escape. Summary of the invention

[0006] In view of the problems of low reverse osmosis efficiency and high energy consumption of traditional ion exchange membranes, the present invention provides a Janus-MoS2@CS / PI composite aerogel and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a Janus-MoS2@CS / PI composite aerogel comprises the following steps: Step 1, preparing polyimide (PI) aerogel by using a sol-gel-freeze drying technique using a polyamic acid (PAA) nanofiber membrane prepared by electrospinning technology; Step 2, preparing a MoS2 nanoflower precursor solution by a hydrothermal method, subjecting the MoS2 nanoflower precursor solution to a gradient heat treatment, and then adding chitosan alcohol (CS) and ultrasonically obtaining a MoS2@CS dispersion; Step 3, the MoS2@CS dispersion is electrostatically sprayed on the polyimide (PI) aerogel by electrostatic spraying, and after drying, the Janus MoS2@CS / PI aerogel with self-powered signal transmission and seawater desalination effects is obtained.

[0008] Further, the specific method for preparing the polyamic acid (PAA) nanofiber membrane by electrospinning technology in the step 1 is: at room temperature, dissolving diaminodiphenyl ether (ODA) in N,N-dimethylformamide (DMF) and stirring until it is clear, then adding 1,2,4,5-pyromellitic anhydride (PMDA) and magnetically stirring to obtain a bright yellow polyamic acid (PAA) spinning solution (20wt%); electrospinning the polyamic acid (PAA) spinning solution at a voltage of 27 kV, with a receiving distance of 15 cm; collecting the nanofiber membrane at a drum speed of 20 rpm, placing the spun polyamic acid (PAA) nanofiber membrane in an oven, and drying it at 80°C for 12 h to remove the residual solvent to obtain the polyamic acid (PAA) nanofiber membrane; the molar ratio of diaminodiphenyl ether (ODA), N,N-dimethylformamide (DMF) and 1,2,4,5-pyromellitic anhydride (PMDA) is 1:1:1; Furthermore, the specific method for preparing the polyimide (PI) aerogel by the sol-gel-freeze drying technology in step 1 is: cutting the polyamic acid (PAA) nanofiber membrane into pieces and mixing it with deionized water to obtain a 1wt% dispersion; breaking up and dispersing the dispersion, adding triethylamine (TEA) and stirring to obtain a light yellow uniform suspension PAAs; rapidly freezing the light yellow uniform suspension PAAs, and then freeze-drying to obtain a PAAs composite aerogel; and performing thermal imidization under nitrogen conditions to obtain a polyimide (PI) aerogel.

[0009] Further, the molar ratio of the triethylamine (TEA) to the polyamic acid (PAA) nanofiber membrane is 1:2-1:3; The specific operation of breaking and dispersing the dispersion is: using a high-speed homogenizer to fully break and disperse the dispersion at a speed of 9000 rpm; The specific operation of rapidly freezing the light yellow uniform suspension PAAs and then freeze-drying it is as follows: rapidly freezing with liquid nitrogen and then transferring to a refrigerator for 4 hours of equilibrium, and then drying in a freeze dryer at -60°C for 48 hours; The specific operation of thermal imidization under nitrogen conditions to obtain polyimide (PI) aerogel is: thermal imidization is performed under nitrogen conditions at a heating rate of 5°C / min at 100°C, 200°C, and 300°C for 1 h respectively, and then cooled to room temperature to obtain polyimide (PI) aerogel.

[0010] Further, the step 2, preparing a MoS2 nanoflower precursor solution by a hydrothermal method, subjecting the MoS2 nanoflower precursor solution to a gradient heat treatment, and then adding chitosan alcohol to ultrasonically obtain a MoS2@CS dispersion; specifically comprises the following steps: Step 2.1, ammonium molybdate ((NH4)6Mo7O 24 ) and thiourea (CH4N2S) were slowly added into deionized water and stirred continuously until they were completely dissolved to form a transparent solution; surfactant hexadecyltrimethylammonium bromide (CTAB) and phytic acid were added into the transparent solution, and then 5 mM urea was slowly added and stirred continuously for 0.5 h to obtain a MoS2 nanoflower precursor solution; Step 2.2, subjecting the MoS2 nanoflower precursor solution to gradient heat treatment, separating the precipitate, washing and vacuum drying to obtain MoS2 nanoflowers; Step 2.3, mixing the MoS2 nanoflowers with deionized water to obtain a suspension; breaking and dispersing the suspension, adding polyvinyl pyrrolidone and stirring, and then slowly adding chitosan alcohol and ultrasonically obtaining a MoS2@CS dispersion.

[0011] Furthermore, the specific operation of the gradient heat treatment in step 2.2 is: at room temperature, heating to 120°C at a heating rate of 1.0°C / min and keeping warm for 2.5 h; then heating to 220°C at a heating rate of 1.5°C / min and keeping warm for 6 h; finally, cooling to room temperature at a rate of 0.5°C / min.

[0012] In the step 2.2, the precipitate is separated, washed and vacuum dried. Specifically, the precipitate is separated, washed with deionized water and ethanol for several times, and vacuum dried at 60°C.

[0013] Further, in step 2.1, ammonium molybdate ((NH4)6Mo7O 24 ) and thiourea (CH4N2S) in a molar ratio of 1:20, 1:40 or 1:60; in the step 2.1, hexadecyltrimethylammonium bromide (CTAB) and ammonium molybdate ((NH4)6Mo7O 24 ) is 1:1, 1:2, 1:4; the phytic acid content in step 2.1 is 5%, 10%, 15% and 20% of the mass of ammonium molybdate; In the step 2.3, the mass ratio of MoS2 nanoflowers, polyvinyl pyrrolidone and chitosan alcohol is 50:1:1; in the step 2.3, the stirring time is 1h and the ultrasonic time is 2h.

[0014] Furthermore, in step 3, the MoS2@CS dispersion is electrostatically sprayed on the polyimide (PI) aerogel by electrostatic spraying, and the specific operation is: The prepared MoS2@CS dispersion was loaded into a syringe, and bubbles were exhausted. The needle was installed and fixed to the liquid supply device, and the liquid supply was slowly pushed until droplets appeared on the needle. The plate spacing was adjusted to 17 cm, the voltage was 15 kV, the liquid supply rate was 0.3 mL / h, and the exhaust was turned on. The voltage was adjusted so that the droplets at the needle were evenly dispersed in a cone-shaped spray. After the electrostatic spray process was stable, the synthesized polyimide (PI) aerogel was electrostatically sprayed. The specific operation of drying in step 3 is: vacuum drying at 60° C. for 24 h, and sealing and storing after drying.

[0015] A Janus-MoS2@CS / PI composite aerogel prepared by the preparation method as described above.

[0016] Application of Janus-MoS2@CS / PI composite aerogel in seawater desalination.

[0017] Application of Janus-MoS2@CS / PI composite aerogel in smart wearable devices.

[0018] Compared with the existing seawater desalination membrane, the present invention has the following advantages: The high temperature resistant PI aerogel was synthesized by electrospinning, sol-gel-freeze drying and heat treatment, and then it was combined with MoS2, which has piezoelectric properties, signal transmission and photothermal conversion effects, by electrostatic spraying to prepare a multifunctional composite aerogel. The aerogel exhibits good evaporation efficiency, excellent evaporation rate and good salt resistance, while overcoming the disadvantage of traditional seawater desalination membranes that they cannot detect the ion concentration in water in real time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of MoS2 nanoflowers that have signal transmission, piezoelectric properties and photothermal conversion properties.

[0020] Figure 2 This is the element distribution map of MoS2 nanoflowers.

[0021] Figure 3 This is the XRD pattern of MoS2 nanoflowers.

[0022] Figure 4 This is the SEM image of PAA nanofibers.

[0023] Figure 5 This is the SEM image of PI aerogel.

[0024] Figure 6 This is the actual picture of Janus-MoS2@CS / PI aerogel.

[0025] Figure 7Mass evaporation diagram of Janus-MoS2@CS / PI aerogel.

[0026] Figure 8 This is the evaporation efficiency and evaporation rate diagram of Janus-MoS2@CS / PI aerogel.

[0027] Fig. 9 Self-power supply and signal transmission test of Janus-MoS2@CS / PI aerogel. DETAILED DESCRIPTION

[0028] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0029] Example 1 Preparation of polyamic acid (PAA) nanofiber membrane using electrospinning technology Preparation of polyamic acid (PAA) nanofiber membrane: First, the electrospinning precursor is prepared by the sol-gel method, and the polyamic acid (PAA) nanofiber membrane is successfully electrospun by adjusting the spinning parameters (spinning concentration, spinning distance, spinning voltage). The specific preparation steps are: 2.24 g of diaminodiphenyl ether (ODA) was dissolved in 14.4 mL of N,N-dimethylformamide (DMF). After stirring at room temperature until clear, an equal amount of 1,2,4,5-pyromellitic dianhydride (PMDA) was added. After magnetic stirring for 24 h, a bright yellow polyamic acid spinning solution (PAA, 20 wt%) was obtained. The obtained spinning solution was electrospun at a voltage of 27 kV with a receiving distance of 15 cm. The nanofiber membrane was collected at a drum speed of 20 rpm, and the spun PAA nanofiber membrane was placed in an oven and dried at 80 ° C for 12 h to remove the residual solvent.

[0030] Among them, diaminodiphenyl ether (ODA) and 1,2,4,5-pyromellitic dianhydride (PMDA) as monomers of PAA nanofibers can be common types in the art, but are not limited thereto.

[0031] Among them, the ratio of each raw material in the PAA spinning solution can be adjusted according to specific needs. The preferred poly (diaminodiphenyl ether) (ODA) is 2.24 g, the mass of 1,2,4,5-pyromellitic dianhydride (PMDA) is 2.72 g, and the concentration of the PAA spinning solution is 26wt%.

[0032] The condition parameters involved in the preparation of polyamic acid (PAA) nanofiber membrane in this embodiment can be selected according to specific needs. In some specific embodiments of the present invention, the specific conditions are: electrospinning voltage is 25 kV, spinning distance is 15 cm, drum speed is 20 rpm, spinning temperature is 23 ° C, and spinning humidity is 45%.

[0033] Example 2

[0034] A method for preparing a Janus-MoS2@CS / PI composite aerogel comprises the following steps: Step 1, preparing polyimide (PI) aerogel by using a sol-gel-freeze drying technique using a polyamic acid (PAA) nanofiber membrane prepared by electrospinning technology; Specifically, 0.5 g of polyamic acid (PAA) nanofiber membrane was cut into pieces and mixed with 50 mL of deionized water to obtain a 1wt% dispersion; the dispersion was fully broken up and dispersed using a high-speed homogenizer at a speed of 9000 rpm, and then 0.5 mL of triethylamine (TEA) was added and stirred for 1 hour to obtain a light yellow uniform suspension PAAs; the light yellow uniform suspension PAAs was transferred into a silica gel mold, quickly frozen with liquid nitrogen, and then transferred to a refrigerator for 4 hours of equilibrium, and then dried in a freeze dryer at -60 °C for 48 hours to obtain a PAAs composite aerogel; thermal imidization was performed under nitrogen conditions to obtain a polyimide (PI) aerogel.

[0035] Step 2, preparing a MoS2 nanoflower precursor solution by a hydrothermal method, subjecting the MoS2 nanoflower precursor solution to a gradient heat treatment, and then adding chitosan alcohol (CS) and ultrasonically obtaining a MoS2@CS dispersion; specifically comprising the following steps: Step 2.1: Add ammonium molybdate ((NH4)6Mo7O) at a molar ratio of 1:20 24 ) and thiourea (CH4N2S) were slowly added into deionized water and stirred continuously until they were completely dissolved to form a transparent solution; surfactant hexadecyltrimethylammonium bromide (CTAB) and phytic acid (phytic acid content was 10% of the mass of ammonium molybdate) were added into the transparent solution, and then 5 mM urea was slowly added and stirred continuously for 0.5 h to obtain MoS2 nanoflower precursor solution; hexadecyltrimethylammonium bromide (CTAB) and ammonium molybdate ((NH4)6Mo7O 24 ) has a molar ratio of 1:2.

[0036] Step 2.2, the MoS2 nanoflower precursor solution was subjected to gradient heat treatment, heated to 120°C at room temperature at a heating rate of 1.0°C / min and kept warm for 2.5 h; then heated to 220°C at a heating rate of 1.5°C / min and kept warm for 6 h; finally cooled to room temperature at a rate of 0.5°C / min. The precipitate was separated, washed with deionized water and ethanol several times, and vacuum dried at 60°C to obtain MoS2 nanoflowers.

[0037] Step 2.3, MoS2 nanoflowers are mixed with deionized water to obtain a suspension; after the suspension is crushed and dispersed, polyvinyl pyrrolidone is added and stirred for 1 hour, and then chitosan alcohol is slowly added and ultrasonicated for 2 hours to obtain MoS2@CS dispersion. The mass ratio of MoS2 nanoflowers, polyvinyl pyrrolidone, and chitosan alcohol is 50: 1: 1.

[0038] Step 3, electrostatically spray the MoS2@CS dispersion on the polyimide (PI) aerogel by electrostatic spraying, load the prepared MoS2@CS dispersion into a syringe, exhaust all bubbles, install the needle, fix it to the liquid supply device, and slowly push the liquid supply until droplets appear on the needle; adjust the plate spacing to 17 cm, the voltage to 15 kV, the liquid supply rate to 0.3 mL / h, and turn on the exhaust; adjust the voltage so that the droplets at the needle are evenly dispersed in a conical spray shape, and after the electrostatic spray process is stable, electrostatically spray the synthesized polyimide (PI) aerogel; vacuum dry at 60°C for 24 h, and seal and store after drying to obtain the Janus MoS2@CS / PI aerogel with self-powered signal transmission and seawater desalination effect.

[0039] Example 3

[0040] Figure 1 The SEM image of the MoS2 nanoflower with piezoelectric, signal transmission and photothermal conversion properties prepared in Example 2 is shown. It can be seen that the two-dimensional nanosheet morphology and extremely large specific area can effectively transmit signals and provide piezoelectric signal transmission and photothermal conversion properties.

[0041] Figure 2 and Figure 3 The EDS and XRD patterns of the MoS2 nanoflowers with piezoelectric, signal transmission and photothermal conversion properties prepared in Example 2 are shown. It can be seen that the EDS shows that the nanoflowers show uniformly distributed Mo, S and O elements, indicating that the synthesized nanoflowers are MoS2. Figure 3In the XRD pattern, obvious diffraction peaks appear at 14.2°, 33.8°, 39.6°, 43.3°, 49.4° and 58.8°, which correspond to the (002), (101), (103), (006), (105) and (110) crystal planes of MoS2 (JCPDS No.75-1539). This also shows that the synthesized nanoflowers are MoS2. In addition, MoS2 shows diffraction peaks of MoP at 27.9°, 32.0°, 42.9°, 57.0° and 73.9°, which clearly shows that part of MoS2 is successfully converted into MoP. This also fully illustrates the successful preparation of MoS2 nanoflowers.

[0042] Figure 4 The SEM image of the PAA nanofibers prepared in Example 1 is shown. The PAA nanofibers present a uniform and smooth surface, and the fiber diameter ranges from 200 to 300 nm.

[0043] Figure 5 This is the SEM image of the PI aerogel prepared in Example 2, in which the porous channels and continuous network structure can provide effective channels for water transmission and gas discharge, which can prevent salt accumulation on the evaporator surface, thereby improving the light absorption performance and steam generation of the system.

[0044] Figure 6 This is a physical picture of Juans MoS2@CS / PI aerogel prepared in Example 2. The upper layer of Juans is black MoS2 nanoflowers, which have excellent light absorption ability and good photothermal conversion effect, and can convert the absorbed solar energy into heat. The lower layer is hydrophobic PI nanofiber aerogel, whose internal network structure and effective channels can accelerate the upward transmission of moisture. The moisture reaching the MoS2 photothermal layer can be effectively converted into water vapor, and converted into clean water when encountering the condensation system.

[0045] Figure 7 and Figure 8 The mass loss graph and evaporation rate graph of Juans MoS2@CS / PI aerogel and pure water prepared in Example 5 are shown respectively. Compared with pure water, the evaporation rate and efficiency of Juans MoS2@CS / PI aerogel are greatly improved, with an efficiency of 97.5% and a rate of 1.43 kg m -2 h -1 The clean water produced by Juans MoS2@CS / PI aerogel under 12 hours of illumination is enough for an adult to drink for 7 days, which also shows that Juans MoS2@CS / PI aerogel has good water purification ability.

[0046] Fig. 9The signal transmission and self-power supply test of Juans MoS2@CS / PI aerogel prepared in Example 5 showed that by gently tapping Juans MoS2@CS / PI aerogel, 20 diodes in series can be easily connected, and voltages of 8 V and 7 V can be generated respectively through foot and arm bending movements. This is enough to show that Juans MoS2@CS / PI aerogel has the ability to self-power and transmit electrical signals.

[0047] Example 4

[0048] The difference from Example 2 is that in step 2.1 of this example, ammonium molybdate ((NH4)6Mo7O 24 ) and thiourea (CH4N2S) in a molar ratio of 1:40; hexadecyltrimethylammonium bromide (CTAB) and ammonium molybdate ((NH4)6Mo7O 24 ) has a molar ratio of 1:4.

[0049] Example 5

[0050] The difference from Example 2 is that in step 2.1 of this example, ammonium molybdate ((NH4)6Mo7O 24 ) and thiourea (CH4N2S) in a molar ratio of 1:60; hexadecyltrimethylammonium bromide (CTAB) and ammonium molybdate ((NH4)6Mo7O 24 ) has a molar ratio of 1:1.

[0051] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A method for preparing Janus-MoS2@CS / PI composite aerogel, characterized in that: The following steps are involved: Step 1, preparing polyimide aerogel by sol-gel-freeze drying technology using polyamic acid nanofiber membrane prepared by electrospinning technology; Step 2, preparing a MoS2 nanoflower precursor solution by a hydrothermal method, subjecting the MoS2 nanoflower precursor solution to a gradient heat treatment, and then adding chitosan alcohol and ultrasonically obtaining a MoS2@CS dispersion; Step 3, electrostatically spray the MoS2@CS dispersion onto the polyimide aerogel by electrostatic spraying, and after drying, obtain the Janus MoS2@CS / PI aerogel with self-powered signal transmission and seawater desalination effects.

2. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 1, characterized in that: The specific method for preparing the polyimide aerogel by the sol-gel-freeze drying technology in step 1 is: cutting the polyamic acid nanofiber membrane into pieces and mixing it with deionized water to obtain a 1wt% dispersion; breaking and dispersing the dispersion, adding triethylamine and stirring to obtain a light yellow uniform suspension PAAs; rapidly freezing the light yellow uniform suspension PAAs, and then freeze-drying to obtain a PAAs composite aerogel; and performing thermal imidization under nitrogen conditions to obtain a polyimide aerogel.

3. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 2, characterized in that: The molar ratio of the triethylamine to the polyamic acid nanofiber membrane is 1:2-1:3; The specific operation of breaking and dispersing the dispersion is: using a high-speed homogenizer to fully break and disperse the dispersion at a speed of 9000 rpm; The specific operation of rapidly freezing the light yellow uniform suspension PAAs and then freeze-drying it is as follows: rapidly freezing with liquid nitrogen, equilibrating for 4 hours, and then drying at -60°C for 48 hours; The specific operation of thermal imidization under nitrogen conditions to obtain polyimide aerogel is: thermal imidization is performed under nitrogen conditions at a heating rate of 5°C / min, at 100°C, 200°C, and 300°C for 1 h each, and then cooled to room temperature to obtain polyimide aerogel.

4. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 1, characterized in that: The step 2 is to prepare a MoS2 nanoflower precursor solution by a hydrothermal method, subject the MoS2 nanoflower precursor solution to a gradient heat treatment, and then add chitosan alcohol to ultrasonically obtain a MoS2@CS dispersion; specifically comprising the following steps: Step 2.1, slowly add ammonium molybdate and thiourea into deionized water and continue stirring until they are completely dissolved to form a transparent solution; add surfactant hexadecyltrimethylammonium bromide and phytic acid into the transparent solution, then slowly add 5 mM urea, and continue stirring for 0.5 h to obtain a MoS2 nanoflower precursor solution; Step 2.2, subjecting the MoS2 nanoflower precursor solution to gradient heat treatment, separating the precipitate, washing and vacuum drying to obtain MoS2 nanoflowers; Step 2.3, mixing the MoS2 nanoflowers with deionized water to obtain a suspension; breaking and dispersing the suspension, adding polyvinyl pyrrolidone and stirring, and then slowly adding chitosan alcohol and ultrasonically obtaining a MoS2@CS dispersion.

5. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 4, characterized in that: The specific operation of the gradient heat treatment in step 2.2 is: at room temperature, heat to 120°C at a heating rate of 1.0°C / min and keep warm for 2.5 h; then heat to 220°C at a heating rate of 1.5°C / min and keep warm for 6 h; finally, cool to room temperature at a rate of 0.5°C / min.

6. In step 2.2, the precipitate is separated, washed and vacuum dried. Specifically, the precipitate is separated, washed with deionized water and ethanol for several times, and vacuum dried at 60°C.

7. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 4, characterized in that: In the step 2.1, the molar ratio of ammonium molybdate to thiourea is 1:20, 1:40 or 1:60; in the step 2.1, the molar ratio of hexadecyltrimethylammonium bromide to ammonium molybdate is 1:1, 1:2 or 1:4; in the step 2.1, the phytic acid content is 5%, 10%, 15% and 20% of the mass of ammonium molybdate; In the step 2.3, the mass ratio of MoS2 nanoflowers, polyvinyl pyrrolidone and chitosan alcohol is 50:1:1; in the step 2.3, the stirring time is 1h and the ultrasonic time is 2h.

8. The method for preparing a Janus-MoS2@CS / PI composite aerogel according to claim 1, characterized in that: In step 3, the MoS2@CS dispersion is electrostatically sprayed on the polyimide aerogel by electrostatic spraying, and the specific operation is: The prepared MoS2@CS dispersion was loaded into a syringe, and bubbles were exhausted. The needle was installed and fixed to the liquid supply device, and the liquid supply was slowly pushed until droplets appeared on the needle. The plate spacing was adjusted to 17 cm, the voltage was 15 kV, the liquid supply rate was 0.3 mL / h, and the exhaust was turned on. The voltage was adjusted so that the droplets at the needle were evenly dispersed in a cone-shaped spray. After the electrostatic spray process was stable, the synthesized polyimide aerogel was electrostatically sprayed. The specific operation of drying in step 3 is: vacuum drying at 60° C. for 24 h, and sealing and storing after drying.

9. A Janus-MoS2@CS / PI composite aerogel prepared by the preparation method according to any one of claims 1 to 7.

10. Use of the Janus-MoS2@CS / PI composite aerogel as claimed in claim 8 in seawater desalination.

11. An application of the Janus-MoS2@CS / PI composite aerogel as claimed in claim 8 in smart wearable devices.